2008
DOI: 10.1109/tgrs.2008.919143
|View full text |Cite
|
Sign up to set email alerts
|

The Compact Polarimetry Alternative for Spaceborne SAR at Low Frequency

Abstract: International audienceIn spaceborne synthetic aperture radar (SAR), a single-polarization on-transmit offers twice the swath width compared to full polarization. This is linked to SAR system design issues, and, without getting into the technical details deserving by themselves a full paper, we can just mention the swath characteristics of ALOS PALSAR (the Advanced Land Observing Satellite, Phased Array L-Band Synthetic Aperture Radar), reducing from 70 km for the dual-pol mode to 30 km for the full polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…However, the results from the CP radar should be better than those from a single-polarized or dual-polarized SAR. Many investigations (Dubois-Fernandez et al 2008;Ainsworth, Kelly, and Lee 2009;Nord et al 2009;Charbonneau et al 2010) have confirmed these results for various applications.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the results from the CP radar should be better than those from a single-polarized or dual-polarized SAR. Many investigations (Dubois-Fernandez et al 2008;Ainsworth, Kelly, and Lee 2009;Nord et al 2009;Charbonneau et al 2010) have confirmed these results for various applications.…”
Section: Introductionmentioning
confidence: 55%
“…Recently, compact polarimetry (CP) has been suggested as an alternative SAR configuration to maintain swath coverage while increasing information content compared to single-polarization or dual-polarization systems (Souyris and Mingot 2002;Raney 2007;Ainsworth, Kelly, and Lee 2009;Dubois-Fernandez et al 2008;Nord et al 2009). The m-delta decomposition for CP data is very similar to the Freeman-Durden decomposition (Charbonneau et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the transmission of a field has a linearly polarized component it will cause uncertainties or omission when classifying dihedral backscatter [96]. Circular polarization transmission is the best way to prevent the rotation of a linearly polarized wave as it transmits through the ionosphere, but some omission may still occur [97]. Therefore, some features will not be as visible in the simulated compact polarimetry data because they are too faint and do not exceed the noise floor.…”
Section: Resultsmentioning
confidence: 99%
“…Fully polarimetric SAR (PolSAR) and also Compact Polarimetric SAR [167][168][169][170] measurements have been used to study the dependence of the polarimetric signature on land cover changes and on surface parameters such as soil moisture and surface roughness. The major advantage of using PolSAR over traditional SAR is its ability to measure all the polarisation characteristics of a surface target simultaneously.…”
Section: Soil Moisture Retrieval Using Polarimetric Parametersmentioning
confidence: 99%